Кримінологічна характеристика та запобігання злочинам проти моральності - Хомич, Д.; Khomych, D. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Статтю присвячено теоретичним аспектам визначення сутності злочинів проти моральності та їх попередження. Розглянуто основні напрями роботи правоохоронних органів щодо попередження злочинів проти моральності. Запропоновані загально-соціальні заходи запобігання злочинам проти моральності як сукупність економічних, політичних, організаційних, інформаційних та інших заходів, які забезпечують розвиток суспільства, обмеження криміногенно-небезпечного протистояння у суспільстві, зміцнення економіки, нейтралізацію чинників виникнення криміногенних середовищ у суспільстві.The article is devoted to the theoretical aspects of determining the nature of offenses against morality and preventing them. Legislative recognition of crimes against morality and establishing criminal responsibility for them is justified by the key principles of criminalization. It was determined that crimes against morality have average level of latency. In the focus of attention are social measures aimed at preventing crimes against morality, which are a set of economic, political, organizational, informational and other measures to ensure development of a society, restricting crime-dangerous antagonism in the society, strengthening the economy, neutralization of the factors which promote the occurrence of criminogenic groups in society. Specific criminological prevention of crimes against morality can be defined as a complex of evidence-based, practical, necessary and actually-implemented measures aimed at preventing potential attacks on morality at all stages of their formation.
Criminological Сharacteristics and Preventive Measures of Crimes Against Morality.
Keywords: моральність; злочин; протидія; спеціальні заходи запобігання злочинам; morality; crime; counteraction; special crime prevention measures; prevention